2014
DOI: 10.5455/ijmsph.2014.290720141
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes: Perinatal and maternal complication in 24-28 weeks

Abstract: Background: Gestational diabetes mellitus (GDM) is a glucose tolerance disorder that occurs or is diagnosed for the first time during pregnancy. Perinatal morbidity is more and women with GDM have more risk of developing diabetes. Uttar Pradesh is a state of India with one of the highest rate of infant as well as maternal mortality which might be, at least partially, due to GDM. Thus, appropriate assessment and management of GDM can improve the outcomes. Aims & Objectives: Primary objective of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
3
15
1
Order By: Relevance
“…There were more Signifi cant( p< 0.0001) Perinatal mortality 597 Mothers. This fi nding was in line with many studies [11][12][13][14][15][16][17][18] In most of the north Indian states, male to female ratio is worse because of female feticide due to centuries-old wish to…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…There were more Signifi cant( p< 0.0001) Perinatal mortality 597 Mothers. This fi nding was in line with many studies [11][12][13][14][15][16][17][18] In most of the north Indian states, male to female ratio is worse because of female feticide due to centuries-old wish to…”
Section: Resultssupporting
confidence: 89%
“…36%) women were Diagnosed Type II Diabetes who have GDM were controlled with >160 mg/dl to 200 mg/dl. This fi nding was in unison with many related studies[5][6][7][8][9][11][12][13][14][15][16][17][18][19][20][21], on GDM that Blood sugar level management is imporatant in pregnancy.The Blood Sugar level at the time of Diagnosis of GDM women is strongly related to Perinatal mortality and increased…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Prevalence was found 6.6% in Jodhpur Rajasthan, 9.7% in Uttar Pradesh, 5.2% in Odisha, 17% in Kollam district Kerala, 14.42% in Kanpur Uttar Pradesh, 6.94% in Jammu Region. [24][25][26][27][28][29] We observed positive association of GDM by age group. A study conducted by Wahi P, et al in Jammu showed that a significant proportion of subjects with GDM were overweight 19 (30.65%) and obese 16 (25.8%).…”
Section: Discussionmentioning
confidence: 95%
“…Gestational diabetes mellitus (GDM) is a condition of glucose intolerance developed during pregnancy . Many women with GDM experience pregnancy‐related complications, which primarily affect the fetus and include macrosomia, congenital malformations, prematurity, neonatal intensive care unit (NICU) admission, and respiratory distress syndrome .…”
Section: Introductionmentioning
confidence: 99%